2018
DOI: 10.1016/j.gie.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2 generational improvements in colonoscopes on adenoma miss rates: results of a prospective randomized multicenter tandem study

Abstract: This randomized tandem trial showed lower adenoma miss rates and higher adenoma detection rates for the newer 190 colonoscopes compared with the 160/5 series. These results suggest that it takes multiple improvements, such as those implemented over 2 instrument generations, before an effect on adenoma (miss) rate can be observed. (Study registration number: ISRCTN 2010-A01256-33.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 48 publications
1
41
0
Order By: Relevance
“…In this regard, a recent crossover trial showed a substantial reduction in adenoma miss rate when skipping 2 generation of colonoscopy system. 15 From a methodology perspective, our study showed a favorable correspondence between the detection and miss rates in the parallel and crossover arms, respectively, and also a somewhat unexpected coherence across all the secondary end-points at both the per-patient and per-polyp level. This result is to be related with a uniform performance of the study endoscopists in the 2 methodological arms, as clearly supported by the similar values in ADR between the 2 parallel arms, on one side, and the 2 crossover arms (first pass), on the other.…”
Section: Discussionmentioning
confidence: 57%
“…In this regard, a recent crossover trial showed a substantial reduction in adenoma miss rate when skipping 2 generation of colonoscopy system. 15 From a methodology perspective, our study showed a favorable correspondence between the detection and miss rates in the parallel and crossover arms, respectively, and also a somewhat unexpected coherence across all the secondary end-points at both the per-patient and per-polyp level. This result is to be related with a uniform performance of the study endoscopists in the 2 methodological arms, as clearly supported by the similar values in ADR between the 2 parallel arms, on one side, and the 2 crossover arms (first pass), on the other.…”
Section: Discussionmentioning
confidence: 57%
“…The majority, 80%, of post colonoscopy cancers are thought to result from missed polyps [5]. There is significant evidence from "back to back" colonoscopy studies to support this suggestion with reported adenoma miss rates ranging from 7% employing newer technologies to 48% for standard colonoscopy [7][8][9][10]. As a result, there is significant effort and energy being employed to enhance technology and improve individual practice to reduce adenoma miss rates.…”
Section: Interval Cancer Rates and Etiologymentioning
confidence: 99%
“…Endoscopists with low adenoma detection rates (ADRs)dan indirect proxy for missed lesionsdhave been associated with a higher risk of postcolonoscopy cancer. 1 Tandem studies have shown that a substantial proportion of neoplastic lesions, ranging from 10% to 30%, 3 are still missed, with <10-mm nonpedunculated lesions representing the most frequently failed-to-detect lesions. 3,4 When lesion recognition is excluded, the main technical pitfalls of diagnostic colonoscopy are still represented by the lack of total visual coverage of the colorectal mucosal resulting from the existence of multiple blind spots.…”
mentioning
confidence: 99%
“…This has also been the unfavorable outcome of several other innovations, such as high definition, wider angle (ie, 140 to 170 ) or electronic chromoendoscopy, forcing some authors to consider that only a fundamental change of the endoscopy system, rather than single improvements, may actually improve the detection rate. 3 In this issue of Gastrointestinal Endoscopy, 6 a highquality randomized tandem trial (J-FUSE) compares the miss rate between FUSE and standard colonoscopy in a multicenter Japanese setting, showing reductions of roughly 50% and 30% of the adenoma miss rate at perpatient and per-polyp analysis, respectively, also favorably affecting the baseline ADR and the postpolypectomy surveillance intervals according to both American and European guidelines. 7 As frequently happens with technical improvements of colonoscopy, 3 most of the advantages of FUSE were related to polyps <5 mm and proximally located, applying to both flat and protruding lesions.…”
mentioning
confidence: 99%